An analysis of determinants of bank loan default of small farmers in the regions of North-West province / Magape Edwin Moshabele - Moshabele, Magape Edwin (2014)
The main objective of the study was to investigate the causes underlining small-farmers default on bank loan repayments in the North West Province. One hundred and sixty farmers were randomly selected to be part of the sample. Questionnaires were issued to both farmers and bank officials. Descriptive statistics, correlation and regression models were used to analyse the data. The overall results indicate that most of the small farmers are in the old age category (58 years on average) with very low educational level. This scenario poses a challenge to the stakeholders in agriculture specifically the succession plan to these elderly people when they leave agriculture due to retirement. It was revealed by the study that the farmers do not keep either financial or production records. The analysis shows that the small farmers lack skills in financial management therefore, they are unable to execute the prerequisite to modern farming which are literacy and numeracy as indicated by Woohall et. al.,( 1985). Most of the respondents have outstanding debt from Agribank yet they received loans from Landbank. Because of their low production and other many responsibilities, they are unable to repay loan instalments thus leading to loan default to their current financial supplier, which is Landbank. Lack of monitoring of loan funds was identified as one of the causes of the farmers Joan default. The analysis also indicates that the small farmers have access to finance but the major problem is lack of financial management skills, more involvement in household responsibilities, and lack of technical assistance from relevant stakeholders like extension officers and project managers from the bank or from the Department of Agriculture. Since the Land bank have no field officers to assist the farmers, it is recommended that the bank should have field officers to assist farmers in their business, especially with production, marketing, financial management and farm management Skills. The inability of the farmers to access good value markets for their products was identified as one of the problems, which led to loan default because the farmers are unable to market their products at the right time for good value in excess of their cost. It is recommended that financial institutions should assist their clients to access better markets for their products for better price which will in turn give them better income in order to repay their loans. === M.Sc. (Agric. Economics) North-West University, Mafikeng Campus, 2005